The investment portfolio for the scheme of Amanah Saham Wawasan 2020 (ASW 2020) for the year 2007 to 2009: a case for Permodalan Nasional Berhad (PNB) / Sofiah Mohd Yusof Palasaygaran - Mohd Yusof Palasaygaran, Sofiah (2010)
This report paper is mainly to study on “THE INVESTMENT PORTFOLIO FOR THE SCHEME OF AMANAH SAHAM WAWASAN 2020 (ASW 2020) FOR THE YEAR 2007 TO 2009: THE CASE FOR PERMODALAN NASIONAL BERHAD (PNB)”. Throughout this case study paper, we will analyze at which companies the funds from scheme Amanah Saham Wawasan 2020 (ASW 2020) has to be channeled by Permodalan Nasional Berhad (PNB). This paper will also analyze how many companies been invested each year, the types of companies and trends of selecting the companies. Besides, from this case study also, we will see the most suitable selecting companies done by Permodalan Nasional Berhad (PNB) by using the dividend and bonus as benchmark in three years back. The most significant of this paper is where the ideas generated, recommendation and justification part, where almost of the information are generated from the master prospectus and annual report of Amanah Saham Wawasan 2020 (ASW 2020) for year 2007 until 2009 with supplement of table and also pie chart.